2007
DOI: 10.1108/01604950710742095
|View full text |Cite
|
Sign up to set email alerts
|

Circulation analysis of an engineering monograph approval plan

Abstract: Purpose -The purpose of this article is to describe the quantitative evaluation of an engineering monograph approval plan using circulation analysis. Design/methodology/approach -The circulation frequency of titles purchased under the approval plan was analyzed, and compared with the circulation frequency of all engineering books during the same time period, purchased both individually and through the plan. Findings -It was found that 23 percent of the approval plan books circulated, compared with 6 percent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…110 In case studies, Brush looked at titles in an engineering monograph approval plan and found that the circulation of mechanically selected titles was more frequent in all categories than the circulation of the books in those areas as a whole. 111 Kamada found both efficiencies and limitations in an approval plan for her Japanese studies collection. 112 Gyeszly experimented with using a vendor's database to determine categories of materials for selection.…”
Section: Selection Processes and Toolsmentioning
confidence: 99%
“…110 In case studies, Brush looked at titles in an engineering monograph approval plan and found that the circulation of mechanically selected titles was more frequent in all categories than the circulation of the books in those areas as a whole. 111 Kamada found both efficiencies and limitations in an approval plan for her Japanese studies collection. 112 Gyeszly experimented with using a vendor's database to determine categories of materials for selection.…”
Section: Selection Processes and Toolsmentioning
confidence: 99%
“…Brush compared the circulation of books purchased on the engineering approval plan to the circulation of books in the engineering collection as a whole to determine the efficiency of a profile or whether the approval plan should be replaced by individual book ordering. 30 Books ordered on the plan were more heavily used, which warranted maintaining the approval plan. The data also revealed that electrical engineering books were not being ordered through the approval plan.…”
Section: Acquisitions Workmentioning
confidence: 99%
“…As various library systems now have increasingly sophisticated data-mining capabilities, a wealth of management data surrounding purchasing records, circulation transactions, and interlibrary loan (ILL) requests has doi:10.5860/crl.76. 6.740 crl14-632 accumulated that has often remained untapped and unrealized for meaningful analytics. By compiling and analyzing these data, we aimed to find better ways to measure our user needs, assess the results of our collection practices, and identify how our users have interacted with library collections.…”
Section: Mining and Analyzing Circulation And Ill Data For Informed Cmentioning
confidence: 99%
“…5 Brush studied circulation data of engineering titles ordered through an approval plan and compared them to the total circulation data of titles in the whole engineering collection (Library of Congress Classification T class) over the same period. 6 The purpose of the study was to assess the value of using approval plans in her library. Adams and Noel studied circulation statistics for collection evaluation purposes by comparing the usage of titles by subject, publisher, and publication date.…”
Section: Literature Reviewmentioning
confidence: 99%